2018
DOI: 10.1101/346627
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ecology, Not Distance, Explains Community Composition in Parasites of Sky-Island Audubon's Warblers

Abstract: 23 1. Haemosporidian parasites of birds are ubiquitous in terrestrial ecosystems, but their 24 coevolutionary dynamics remain poorly understood. If species turnover in parasites occurs at a 25 finer scale than species turnover in hosts, widespread hosts would encounter diverse parasites 26 and potentially diversify as a result. Previous studies have shown that some wide-ranging hosts 27 encounter varied haemosporidian communities throughout their range, and vice-versa. However, 28it remains difficult to test s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 1 publication
2
7
0
Order By: Relevance
“…This is consistent with Williamson et al. () who found that probability of infection by Parahaemoproteus decreased with elevation in New Mexico sky‐island Audubon's warblers. One possibility could be that S. c. coronata do not cope as well in high elevation environments.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is consistent with Williamson et al. () who found that probability of infection by Parahaemoproteus decreased with elevation in New Mexico sky‐island Audubon's warblers. One possibility could be that S. c. coronata do not cope as well in high elevation environments.…”
Section: Discussionsupporting
confidence: 91%
“…This means these young birds were infected on the breeding ground, as opposed to their wintering grounds, suggesting that infection occurs in the nest or soon after fledging. This is supported by a recent study on Setophaga coronata auduboni in New Mexico (US) sky islands that found a high diversity of haemosporidian lineages but no bird infected by hDENPEN02 (Williamson et al., ).…”
Section: Discussionmentioning
confidence: 58%
“…Fournier et al., 2016) and parasite communities (e.g. Williamson et al., 2019). Our models support this idea by suggesting that the regional species pool, and ecological selection in terms of both habitat suitability and biotic interactions are important for structuring communities.…”
Section: Discussionmentioning
confidence: 99%
“…These parasites can reduce the fitness of their hosts, even in low-level chronic infections (42), and are thought to have the potential to shape avian biogeographic patterns (40,43). Hemosporidian communities in turn are thought to be influenced to varying degrees by host community, climate, and barriers to dispersal (44)(45)(46)(47)(48)(49)(50)(51), but improved modeling frameworks with new data are needed to reciprocally test the causes of host and parasite turnover across biodiverse, tropical landscapes.…”
Section: Significancementioning
confidence: 99%